PERCEPTIONS, FEASIBILITY AND ACCEPTABILITY OF MICRO-CREDENTIALS IN GLOBAL HEALTH GRADUATE EDUCATION - Komeiha, Menna (My University, 2025)
Background Global health presents a challenging environment involving multiple stakeholders with conflicting interests, necessitating soft skills such as incisive decision-making. Micro-credential modules offer an opportunity to equip global health students with these skills. Recognizing this, McMaster University's global health graduate program developed two micro-credential modules focusing on incisive decision-making and international collaboration. This study aimed to evaluate the feasibility and acceptability of micro-credentials as tools to enhance and assess learners' soft skills by examining students' perceptions and experiences. Methods Two asynchronous micro-credential modules focusing on the international collaboration and incisive decision-making skills were developed and piloted using Avenue to Learn (A2L). Pre- and feedback surveys, and interviews, were utilized to evaluate students' overall perceptions of the micro-credential modules. These methods also aimed to identify barriers to participation, offering insights into the factors that influenced students' engagement with the modules. Results The pre-survey received 15 responses, the feedback survey received 8 responses, and 3 individual interviews were conducted. The findings revealed that students were not familiar with the concept and purpose of micro-credential modules. The primary enrollment motivator was career advancement. However, time constraints and competing priorities were identified as significant barriers to participation. Students suggested that future modules could benefit from incorporating an in-person component to facilitate interactive discussions. Overall, micro-credential modules were perceived as an acceptable method for developing soft skills among global health students. Conclusion Micro-credential modules were identified as an acceptable and feasible method for enhancing students' soft skills. Time constraints were cited as a significant barrier to participation. To improve engagement, it is recommended that future modules be introduced before the commencement of the Global Health graduate program's academic coursework. Additionally, adopting a hybrid delivery approach is suggested, combining in-person interactive elements to facilitate direct interactions and idea exchange with an asynchronous online component to provide flexibility.
Keywords: Micro-credentials; Incisive decision-making; Global Health; Graduate education